The Incidence of Land Use Regulations (2021)
I study the welfare consequences of land use regulations for low- and high-skilled workers within a city. I use detailed geographic data for Cook County and Chicago in 2015-2016, together with a spatial quantitative model with two types of workers and real estate developers who face regulations. For identification, I use the 1923 Zoning Ordinance, which was the first comprehensive ordinance in Chicago. I find that an increase of 10 percentage points in the share of residential zoning in a block group, relative to block groups with more commercial zoning, leads to a 1.7% increase in housing prices, a 2.6% decrease in wages and a higher concentration of high-skilled residents. Welfare changes can be decomposed into changes in housing prices, sorting, wages and land rents. Results suggest that more mixed-use zoning and looser floor-to- area limits lead to welfare improvements, especially for low-skilled residents, and to a reduction in welfare inequality.